PENGARUH PERMAINAN KUBUS BERGAMBAR TERHADAP KEMAMPUAN BERHITUNG PERMULAAN ANAK USIA 5-6 TAHUN DI RA AL UBUDIYAH PEKANBARU - Syukri, Dewi; Jas, Jaspar; Chairilsyah, Daviq (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aimed to determine the effect of the display cube games count kemapuan beginning 5-6 years old children in RA Al Ubudiyah. The population in this study were all children aged 5-6 years in school RA Al Ubudiyah Pekanbaru 2nd semester class B TP 2015/2016. The sample in this study is a first class consisting of 5 girls and 17 boys. A total of 22 children in a class B RA Al Ubudiyah participated in this study. This research is a Pre-Experiment by using design One Group Pretest Posttest that the sample was given an early test in advance to determine the ability of an earlier pilot then treated, after being given the treatment were then given a final test, thus the results of the treatment can be known more mutually agree because it can be compared with the situation before and after being treated. Data collection techniques were used that observation. Data analysis technique using large-scale testing and analysis of statistical methods with SPSS for Windows Ver. 20. Based on the results obtained by testing the hypothesis that there is influence sigifikan the beginning numeracy skills of children aged 5-6 years after using the game cube display. N-Gain is the difference between the pretest and posttest. Gain score indicates Tertiary treatment effectiveness. Based on the above results obtained mean value G 50.97% Game Cube display big influence on numeracy skills children aged 5-6 years beginning at RA Al Ubudiyah Pekanbaru.Keywords: Game Cube, numeracy, perception